2023
DOI: 10.1111/febs.16949
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous structural replacement of the sphingoid long‐chain base and sterol in budding yeast

Yushi Kono,
Yohei Ishibashi,
Shizuka Fukuda
et al.

Abstract: The basic structures of membrane lipids that compose biomembranes differ among species; i.e., in mammals, the primary structure of long‐chain base (LCB), the common backbone of ceramides and complex sphingolipids, is sphingosine, whereas, in yeast Saccharomyces cerevisiae, it is phytosphingosine, and S. cerevisiae does not have sphingosine. In addition, the sterol, which is coordinately involved in various functions with complex sphingolipids, is cholesterol in mammals, while in yeast it is ergosterol. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that there may be an interplay between lipids and PMA1 in fungi. PMA1 is reported to localize in lipid microdomains of the plasma membrane, and studies in Saccharomyces cerevisiae have shown that the efficient function of PMA1 is greatly dependent on sphingolipids [36,37]. However, the relationship between plasma membrane H + -ATPase and LD formation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that there may be an interplay between lipids and PMA1 in fungi. PMA1 is reported to localize in lipid microdomains of the plasma membrane, and studies in Saccharomyces cerevisiae have shown that the efficient function of PMA1 is greatly dependent on sphingolipids [36,37]. However, the relationship between plasma membrane H + -ATPase and LD formation remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…PMA1 has been reported to be localized in the lipid microdomains of the plasma membrane, and studies in Saccharomyces cerevisiae have shown that the efficient function of PMA1 is greatly dependent on sphingolipids [27,36]. Abnormally high ergosterol accumulation at the plasma membrane disrupts the structures of lipid rafts, resulting in the mislocalization of PMA1 in cells [15,27,37]. However, the relationship between plasma membrane H + -ATPase and LDs is not fully understood.…”
Section: Introductionmentioning
confidence: 99%